Assessment question generator for primary school mathematics : for the topic decimal - Yu, Jianqi. (2012)
Since beginning in 1969, the Internet has a great growth to tens of millions computer systems from four host computer systems. With the rapid rising, broadband connection has become a common sight around the world as more and more people are taking advantage of the wonderful technology. Web-based applications start attracting more and more attention now because of its huge convenience and flexibility. In this report, detailed information about a web-based system of an assessment question generator for primary school mathematics will be presented. In comparing with the current hardcopy assessment books, this system offers more options including an eLearning environment, online grading system, unlimited practice questions and step-by-step solutions and also providing the ability to generate worksheets for students to practice offline by specifying their own needs. The detailed methodology framework of the web system will be described in this report with focus on topic “decimal” and the design and implementation procedures will also be analyzed including class, database and web interfaces.